Respon Pertumbuhan dan Hasil Tanaman Mentimun (cucumis sativus L.) Varietas Zatavy F1 terhadap Nutrisi Berbeda pada Sistem Hidroponik - Asep Ikhsan Gumelar; Engkus Kusnadi; Lusiana Lusiana (Paspalum: Jurnal Ilmiah Pertanian, 2021)
This study aims to determine the effect of fertilizing nutrients that can increase the growth and yield of cucumber (Cucumis sativus L.) with hydroponic techniques. The research was conducted at the screen house of the Biotechnology Lab Research and Development Division of PT East West Seed Indonesia, in Benteng Village, Campaka District, Purwakarta Regency. This research was conducted in December 2017 until March 2018. This study used a randomized block design (RBD) with 9 replications. Planting factor is a nutrient solution consisting of N1 enza nutrition, N2 alfesindo nutrition, and N3 ewindo nutrition. Parameters observed were plant height, plant dry weight, fruit length, fruit diameter, number of planted fruit and crop fruit weight. The media used in this study was roasted husk charcoal. The results showed that the response of nutrient solutions was significantly different from observations of plant height, whereas the response of nutrient solutions to observations of dry weight, fruit length, fruit diameter, number of fruit plantations and fruit weight of plantations were not significantly different. The results showed that the best nutritional solution was ewindo nutritional solution.